Employing a Carbon-Based Nanocomposite as a Diffusive Solid-Phase Extraction Adsorbent for Methamphetamine for Therapeutic Purposes - Kala, K. Lakshmi; Anbuchezhiyan, G.; Pingili, Kavitha; Singh, Pradeep Kumar; Vel, V. M.; Yusuf, Kareem; Aljuwayid, Ahmed Muteb; Islam, Md Ataul; Christopher, David (Adsorption science & technology, 2023)
Due to the obvious minimal doses of drugs in biological matrices as well as the societal difficulties caused by methamphetamine usage, methamphetamine identification is critical in clinical and forensic laboratories. Because of their simple and inexpensive production procedure, as well as their excellent selectivity and sensitivity, polymeric carbon-based nanocomposites are strong contenders for the diffusive solid-phase extraction approach. The diffusive solid-phase extraction absorbent nanographene oxide polypyrrole composite was produced and used to recover methamphetamine from a complicated urine substrate. The generated NGPPC was fully characterized, and the significant extracting parameters have been explored using the one-parameter-at-a-time strategy. NGOPC is being used to extract methamphetamine using a urine medium with high efficiency. The NGPPC synthesizing procedure was easy, and the extraction method will demonstrate good repeatability. Moreover, the practical and efficient synthesis process stimulates the use of carbon-based compounds in various extraction procedures. As for detecting and quantifying equipment, HPLC monitors are being used. 300 mL methanol, 7 min extracting and desorption duration, 5000 mixing frequency, urinary pH value of 20, 40 mg adsorption, and 5 mL amount of urine were the optimal extraction variables. Following tracing the calibration graph, the method’s linear ranges were determined to be 40-600 ng/ml. The detection limits (LOD) and quantitation limits (LOQ), correspondingly, were 10 and 35.80 ng/mL. The proposed methodology seemed to have a detection range of 9 ng/mL. The suggested approach’s applicability in numerous characterization and medical facilities was proven by the examination of addicted subjects using the proposed technique. For successful extraction of methamphetamine using biological urine samples, the carbon-based adsorbent was being used as diffusive solid-phase extraction adsorption.